Peningkatan Kinerja UMKM Melalui Pelatihan Manajemen Persediaan: Sasaran UMKM Makanan dan Minuman di Kota Palembang - Ruth Samantha Hamzah; Efva Octavina Donata Gozali; Anisa Listya; Asfeni Nurullah; Patmawati (Sriwijaya Accounting Community Services, 2024)
Inventory management for Micro, Small, and Medium Enterprises (MSMEs) often faces challenges such as surplus or inadequate stock, difficulty in sourcing available products, and navigating inventory amidst fluctuating demand and supply dynamics. Hence, we initiated a community service activity aimed at bolstering the performance of food and beverage MSMEs in Palembang, South Sumatra, through comprehensive inventory management training. This activity engaged 25 MSMEs as participants. The methodology adopted comprised a combination of lectures, tutorials, discussions, and simulations. The outcomes revealed that over 70 percent of the participating MSMEs observed a notable enhancement in their comprehension of inventory management. The objective of this training is to foster better inventory management practices among MSMEs, which in the long run, will influence on factors such as cash flow management, pricing strategies, and optimal stock levels